Variation of physical properties of fruits with drying and kinetic study - Guiné, Raquel (2018)
Background: Food drying, despite being a very ancient practice for food preservation, is still one of the most important processing operations in the food industry. Objective: In this work was studied the drying of two fruits (kiwi and apple) with respect to the physical properties of texture and colour, and the drying kinetics was also evaluated with adjust- ment to thin layer models. Method: For drying, a convection chamber was used at 80 °C and with an air flow of 0.5 m/s. Before and after drying the fruits were analysed with respect to their colour and texture, for being properties that are greatly affected by this type of thermal process. The colour measurement was done with a colorimeter in the CIELab coordinates and for the analysis of the texture profile a texturometer equipped with a 75 mm probe was used. Results:The results showed that the drying caused very noticeable colour differences in both cases, with values of ∆E equal to 8.6 and 10.7, respectively for kiwi and apple. In the case of kiwi, there were important differences between the pulp, the inner part of the fruit and the seeds (L* varying between 42 and 62, a* between -8 and -1, b* between 17 and 33). Regarding the texture, drying produced important changes in the structure of the fruits, with decreasing hardness (40- 62%) and chewiness (13-42%), counterbalanced by an increase in resilience (226-131%), cohe- siveness (17-25%) and elasticity (20-23%). In relation to the kinetics, the two fruits tested had a similar behaviour, taking 2.5 hours to reach a moisture content of about 20%. The Wang & Singh model, with correlation coefficients of 0.997 and 0.999, respectively, for kiwi and apple, was the most suitable to fit the experimental data. Conclusion: Drying significantly affected colour and texture of both fruits and the fitting of the drying data to both kinetics models was successful.